Prioritization of Storage Hydropower Projects under Study in Nepal - Kaini, Surendra; Sapkota, Rajesh; Mishra, Anjay Kumar (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
This research aims to find out the factors hindering the storage hydropower projects and prioritize the storage hydropower projects of Nepal. The study has covered six major storage hydropower projects that are under study. Uttar Ganga Storage Hydroelectric Project and Budigandaki Storage Hydroelectric Project are located in Gandaki Province. Dudhkoshi Storage Hydroelectric Project and Tamor Storage Hydroelectric Project lie in Province 1, while Nalsaugad Storage Hydroelectric Project lies in Karnali Province. These all projects are in the stage of feasibility study. The methodology of research followed Analytical Hierarchy Process (AHP) based on Multi Criteria Decision Making (MCDM). Literature review was done with AHP application in different sector including hydropower. Besides this, reviews were done on aspects like energy crisis, present energy status and future demand. Likewise, pair wise comparison was done in different multiple criteria. Additionally, response from client and expertise opinion were conducted. Technical, financial, environmental, policy and political uncertainties and responses from the project personnel were the major criteria that can affect the priority of the storage hydropower projects. Among the factors, Technical Factor was given the highest importance to be considered for the development of storage hydropower project. The findings of the research revealed that Nalsaugad Storage Hydropower Project to be the best on the basis of the multicriteria considered. The sensitivity analysis with respect to factors was done, which shows no significant difference in the ranking of projects at base case and at the case of change in weight of factors. This research is expected to assist by project managers, project directors, and concerned government authorities in prioritizing the storage projects of Nepal. How to cite this article:  Kaini S, Sapkota R, Mishra AK. Prioritization of Storage Hydropower Projects under Study in Nepal. J Adv Res Geo Sci Rem Sens 2021; 8(1): 1-15. DOI: https://doi.org/10.24321/2455.3190.202101